REVIEW OF SELF-HEALING MATERIAL - SANTOSH PRABHAKAR RAHANE (International Journal of Innovations in Engineering Research and Technology, 2021)
Composites have been widely used in tremendous engineering fields because of their advantages including light weight,process transformationand chemicalstability in anyatmospheric conditions. Due to longdurability and reliability of polymeric material it still problematic when they serve for structural application. Comparatively, microcracking is oneof the fatal deteriorations generated in service,whichbring about catastrophic failure of the materialand hence significantly shorten lifetimesof the structures.Since the damage is deep inside material which isdifficultto be perceived and to repair in particular, thematerialshad better to haveself-healingability.While the development of self-healing materials is progressing at a rapid rate, most successful examples of self-healingsare heavily reliant on polymers from petroleum precursors. Hence, in this work, we undertake the first concerted effort to develop self-healing polymers and composites.Lightweight, high strength, high stiffness fiberreinforced polymer composites are leading contenders as component materials to improve the efficiency and sustainability of many forms of transport